Corporate Governance in the 21st Century: How Technological Disruption is Shaping Corporate Control - Fauzzia, Willma; Waspada, Ikaputera; Sari, Maya (Lembaga Penerbit Fakultas Ekonomi dan Bisns, Universitas Trisakti, 2025)
This article explores the influence of disruptive technologies, such as artificial intelligence (AI), blockchain and big data, on corporate governance in the 21st century. Findings from the literature review show that these technologies increase transparency, accountability and efficiency in the management of companies. Blockchain enables irreversible recording of transactions, reducing the risk of data manipulation and increasing trust between management and stakeholders. Meanwhile, AI and big data support more evidence-based decision-making by analyzing big data to provide deep insights into company performance. However, the adoption of these technologies also faces challenges, including privacy risks, data security and algorithm bias. To maximize the benefits and overcome these challenges, companies are advised to develop comprehensive policies and implement strict security measures. This conclusion emphasizes the need for a strategic approach in integrating disruptive technologies to achieve better and sustainable performance.